2002
DOI: 10.3177/jnsv.48.498
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of a Dietary Assessment Method: The Application of a Digital Camera with a Mobile Phone Card Attachment

Abstract: SummaryThis study was aimed at evaluation of the validity and reliability of an alter native dietary measurement method that assists epidemiologic studies. We validated a handheld personal digital assistant with camera and mobile phone card, called Wellnavi, in which a 1-d weighed diet record was employed as a reference method. Twenty college stu dents majoring in food and nutrition participated in this study. They were asked to keep a diet record and to take digital photos of all these recorded food at the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
101
1
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(115 citation statements)
references
References 12 publications
5
101
1
8
Order By: Relevance
“…Using the photographic food record method, we found that carbohydrate under-and overestimation were the same as the diet diary but fat overestimation was much less prevalent. The Spearman's correlation coefficients between the diet diary and the photographic food records for total energy, macronutrients, micronutrients and fiber reported herein are lower than those reported previously in an adult photographic food record study (Wang et al, 2002). However, the participants in this adult study were all college-aged nutrition students who, due to their age and education level, would be expected to follow the study instructions more closely than a broad population of school-aged children and who, due to their specific nutrition training, would also be more capable of keeping an accurate food diary than our study population.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Using the photographic food record method, we found that carbohydrate under-and overestimation were the same as the diet diary but fat overestimation was much less prevalent. The Spearman's correlation coefficients between the diet diary and the photographic food records for total energy, macronutrients, micronutrients and fiber reported herein are lower than those reported previously in an adult photographic food record study (Wang et al, 2002). However, the participants in this adult study were all college-aged nutrition students who, due to their age and education level, would be expected to follow the study instructions more closely than a broad population of school-aged children and who, due to their specific nutrition training, would also be more capable of keeping an accurate food diary than our study population.…”
Section: Discussioncontrasting
confidence: 50%
“…Two studies have attempted to validate the use of photographic recording as a method of assessing dietary intake in adults (Kaczkowski et al, 2000;Wang et al, 2002). This method seems well suited for pediatric studies as it would considerably decrease the reporting burden for children and their parents and may increase the accuracy of collected data.…”
Section: Introductionmentioning
confidence: 99%
“…The devices were used by adult participants to take photographs of food and drink items and were sent to dieticians alongside descriptions of what was consumed for retrospective portion size and subsequent nutrient intake analysis. Rollo et al (16) noted that the use of voice recordings to describe what was consumed was often insufficient for the coding of data whereas Wang et al (15) observed good agreement when descriptions of items consumed were provided by participants (using a stylus to write on the photographs captured by the PDA) alongside photographs of meals compared to a 1 day food diary.…”
Section: A Comparison Of Food Portion Size Estimation By Older Adultsmentioning
confidence: 99%
“…The majority of these analysis techniques are still being developed and may take some time before they can be applied to dietary assessment as challenges such as the positioning of food on a plate and the differentiation of foods of a similar colour have proven difficult to overcome. Wang et al (15) and Rollo et al (16) investigated the feasibility of the use of Personal Digital Assistant (PDA) and mobile phone devices respectively to remove the onus of portion size assessment necessary for dietary assessment from the participant. The devices were used by adult participants to take photographs of food and drink items and were sent to dieticians alongside descriptions of what was consumed for retrospective portion size and subsequent nutrient intake analysis.…”
Section: A Comparison Of Food Portion Size Estimation By Older Adultsmentioning
confidence: 99%
“…Mobile computing devices such as personal digital assistants (PDAs) and smart phones with cameras are poised to show their potential as a general purpose computing device. PDAs are ideal as a field data collection device (Wang et al, 2002;Kretsch et al, 2004;Kikunaga et al, 2007). In 2004, a survey by Quality Education Data Inc. found that 28% of US school districts offered handheld computers for student and teacher use (Burke, 2005).…”
Section: Introductionmentioning
confidence: 99%